Chronic Imbalance? Gender Disparities in Gastroenterology Across a Decade of the Visceral Medicine Congress in Germany - Gill, Jennifer; Pueschel, Lea; Witte, Marie-Louise; Terjung, Birgit; Lynen Jansen, Petra; Wedemeyer, Heiner; Lenzen, Henrike; Wiestler, Miriam (Zeitschrift für Gastroenterologie, 2025)
Despite efforts toward gender equality, disparities persist in medical careers and leadership. This study examines gender representation in gastroenterology at the German Visceral Medicine Congress from 2013 to 2024, focusing on changes over time.Programs from 1,333 sessions were analyzed for gender ratios of speakers and chairs, including plenary, ab-stract, and industry sessions, plus congress presidents and awardees. Trends were assessed via linear regression and Cochran-Armitage tests.Trend analysis revealed a significant increase in female speakers (r²=0.599, p=0.005) and chairpersons (r²=0.747, p<0.001). Female speaker proportions rose significantly in plenary (r²=0.600, p=0.005), abstract (r²=0.445, p=0.025), and industry sessions (r²=0.641, p=0.003), but did not reach parity. Female chairs showed stronger upward trends: plenary (r²=0.807, p<0.001), abstract (r²=0.490, p=0.016), industry (r²=0.729, p<0.001). Congress presidencies remained all male, and 75–93% of awards went to men.Female representation, especially in chair roles, has improved since the 2019 parity resolution but remains insufficient in key areas. Ongoing gender-sensitive planning and support are needed to foster a more inclusive academic environment.
Keywords: gender gap; gender disparities; visceral medicine congress; gastroenterology; women in medicine